2003
DOI: 10.1037/0022-0167.50.2.156
|View full text |Cite
|
Sign up to set email alerts
|

Motivational attributes of occupational possible selves for low-income rural women.

Abstract: To explore the influence of theorized motivational properties of possible selves on participants' perceived likelihood of achieving their most hoped-for self and avoiding their most feared self, the authors surveyed 198 low-income rural women attending either adult basic education classes (DHS, n ϭ 95) or community college developmental classes (DEV, n ϭ 103), who provided demographic information and completed questionnaires about occupational possible selves and personal efficacy. Affect, knowing someone in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 26 publications
3
38
0
1
Order By: Relevance
“…The energy release certainly seemed to contribute to their increased positivity and momentum. Goals have been shown to have an impact on a range of factors associated with career change including increased motivation (Strauss, Griffin & Parker, 2013), resilience (Locke & Latham, 1990) and the ability to identify the steps needed to achieve them (Robinson, Davis & Meara, 2003), and the findings from this study confirm the importance of clear goal setting for career changers.…”
Section: Implications For Career Confidencesupporting
confidence: 69%
“…The energy release certainly seemed to contribute to their increased positivity and momentum. Goals have been shown to have an impact on a range of factors associated with career change including increased motivation (Strauss, Griffin & Parker, 2013), resilience (Locke & Latham, 1990) and the ability to identify the steps needed to achieve them (Robinson, Davis & Meara, 2003), and the findings from this study confirm the importance of clear goal setting for career changers.…”
Section: Implications For Career Confidencesupporting
confidence: 69%
“…A well-established, reliable coding scheme developed by Oyserman and colleagues (Hooker, 1999;Oyserman et al, 1995;Oyserman & Markus, 1990a, 1990bOyserman & Saltz, 1993;Robinson, Davis, & Meara, 2003) and which was based on earlier systems by Little (1983), Klinger (1975) and Greene (1986), was used to analyze the data. Each expected and feared self was coded into one of the following six thematic content categories: 1.…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…A study of welfare recipients, for instance, found that those who feel empowered in making career choices are likely to devote more time to career development (Hodge, 2001). Similarly, a study of low-income women found that those who feel they have self-determination in their lives are more likely to believe they can achieve their career objectives (Robinson, Davis, & Meara, 2003). This study also suggests that knowing someone in the target occupation increases one's sense of effi cacy.…”
Section: Self-effi Cacymentioning
confidence: 73%